Chronic ozone exposure does not alter sexual behavior but modulates oxidative stress and early testicular apoptosis in adult male rats - Yardimci, Ahmet; Ertugrul, Nazife Ulker; Akkoc, Ramazan Fazil; Tektemur, Nalan Kaya; Tektemur, Ahmet; Guzel, Elif Erdem; Ogeturk, Murat (Elsevier, 2026)
Ozone (O3) has been used to treat various diseases for many years, with most preclinical studies focusing on its effects in conditions such as testicular torsion and ischemia-reperfusion injury; however, its impact on male reproductive function, particularly sexual behavior, remains largely unexplored. This study aimed to evaluate the effects of chronic O3 exposure on sexual behavior, reproductive parameters, oxidative stress, and apoptosis in adult male rats. Animals were assigned to a vehicle group (n = 7), which received saline, or an O3-treated group (n = 7), which received intraperitoneal injections of an O2/O3 mixture (1 mL containing 150 mu g/kg O3) three times per week for eight weeks. Behavioral assessments conducted at the end of the treatment period showed that chronic O3 exposure did not alter appetitive or consummatory sexual behaviors; however, it significantly reduced serum testosterone levels, increased serum total oxidant status (TOS), and decreased testicular hydrogen peroxide (H2O2) levels, suggesting a hormetic response. Additionally, O3 treatment altered apoptotic markers without causing histopathological damage, indicating the onset of early-stage apoptosis. Overall, O3 exposure did not adversely affect sexual behavior independently of testosterone levels in adult male rats, but its induction of oxidative stress and early apoptosis highlights the need for further studies to clarify underlying mechanisms and establish long-term safety.
Keywords: Ozone; Sexual behavior; Oxidative stress; Apoptosis; Hormetic response